Three-year results from the Retro-IDEAL study: real-world data from diabetic macular edema (DME) patients treated with ILUVIEN® (0.19 mg fluocinolone acetonide implant) - Augustin, Albert J.; Khoramnia, Ramin (European journal of ophthalmology, 2020)
Introduction: The Retro-IDEAL (ILUVIEN Implant for chronic DiabEtic MAcuLar edema) study is a retrospective study designed to assess real-world outcomes achieve...
Article first published online: March 18, 2019
Gesehen am 08.07.2020
Das Zeichen ® steht für "registriertes Warenzeichen" und ist im Text hochgestellt